Factors related to recovery knowledge and attitudes among professionals in mental health in Japan. Issue 2 (27th August 2019) - Chiba, Rie; Umeda, Maki; Goto, Kyohei; Miyamoto, Yuki; Yamaguchi, Sosei
Abstract: Aim: To explore what factors may influence recovery knowledge and attitudes among professionals in mental health. Methods: We utilized an existing dataset from a study that surveyed 331 subjects among 475 eligible professionals. We used data from 289 participants without missing values for the analyses (valid response rate = 60.8%). The questionnaire included three psychometrically tested scales: (a) Recovery Knowledge Inventory (RKI); (b) Recovery Attitudes Questionnaire (RAQ); and (c) Internal Work Motivation, as well as other variables. Mean‐based comparisons of the RKI and RAQ scores between several subgroups were examined. We also examined the correlation between RKI and RAQ scores and the continuous variables. Multiple linear regression was implemented to examine the simultaneous effects of the factors on RKI and RAQ scores. The mean age of participants was 39.9 years and 69.2% were female and 44.0% were nursing professionals. Results: Multiple linear regression analyses showed that the internal work motivation and the experience of discharging patients after a lengthy hospitalization were significantly and positively associated with recovery attitude. Working at community facilities and being young were significantly and weakly correlated with recovery knowledge. The experience of participation in self‐help groups exhibited positive relationships with RKI and RAQ scores, while education exhibited positive but weak relationships with RKI and RAQ scores. No significant relationship was observed in the regression analyses. Conclusions: Internal work motivation, the experience of discharging patients after a lengthy hospitalization, working at community facilities, and being young may positively contribute to better recovery knowledge and attitudes. Future research using a longitudinal design will explore other factors.